Heavy metals induced mitochondrial dysfunction in animals: Molecular mechanism of toxicity. (15th March 2022) - Sun, Qiuyu; Li, Ying; Shi, Lijun; Hussain, Riaz; Mehmood, Khalid; Tang, Zhaoxin; Zhang, Hui
Abstract: Heavy metal pollution not only poses a serious threat to both animal growth and public health, but also to aquatic life. Mitochondria are the first target sites for a variety of heavy metals, and recently great attention has been made on the mechanisms of toxicity of heavy metals on mitochondria. The underlying molecular mechanisms of heavy metals that may induce abnormal mitochondrial functions combined with different other environmental pollutants in the body reached a certain level, result in stunted growth and development, abnormal physiological and biochemical changes, over expression of genes, altered behavior and series of toxicological effects including inadequate metabolism. The heavy metals alter mitochondrial membrane permeability, generate increased amount of reactive oxygen species (ROS), by changing the structure of ROS clearance enzyme (antioxidant enzymes) to inhibit its activity. Due to rapid and increased generation of ROS and decreased status of antioxidant enzymes, different environmental pollutants accumulate in the exposed organisms and lead to induction of oxidative stress on the mitochondria. The increased generation of ROS also causes damage to mitochondrial respiratory chain, oxidative phosphorylation decoupling, ATP synthesis disorders, and mitochondrial apoptosis. This review mainly expounds various molecular mechanisms and progress of mitochondrial functional damage to explore the molecular mechanisms of heavy metal damage to mitochondrial functions, which provides a basis for the treatment of heavy metal poisoning, and protects the animal and animal-derived food safety from the source.